Epistemological analysis of theses and dissertations in two Brazilian physical education stricto sensu graduate courses on persons with disabilities Análise Epistemológica de Teses e Dissertações de Dois Programas de Pós-Graduação Stricto Sensu da Educação Física sobre Pessoas com Deficiência - Barbosa D.G.* (2016)
© 2016, Associacao Brasileira de Pesquisadores em Educacao Especial. All rights reserved.This study aimed to identify the methodological approaches and epistemological assumptions adopted by the authors of theses and dissertations on people with disabilities of the two best-ranked stricto sensu graduate programs of Physical Education in Brazil over the last 10 years. The studies were classified according to empirical-analytic, phenomenological-hermeneutic and critical-dialectic methodological approaches. The epistemological analysis was based at scientific validation criteria, conception of causality and conception of science. The investigation identified that 66.7% of the studies used empirical-analytic approach, and 33.3% used phenomenological hermeneutic approach. No studies were found using critical-dialectical approach. It is suggested that researchers’ training in Graduate Physical Education courses, which address the theme people with disabilities, diversify the methodological choices; be based on epistemological assumptions under philosophical perspectives of knowledge, and seek not only objectivity and scientific neutrality.